Analisis Pembentukan Portofolio Optimal Berbasis Single Index Model Untuk Pengambilan Keputusan Investasi - Deni Agus Kristianto; Mustanwir Zuhri (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2018)
This research aims to configure an optimal stock portfolio as the foundation of investment decision on the stocks of the companies that are incorporated in LQ 45 Index in Indonesia Stock Exchange. The portfolio that was configured would later be compared to the market (JKLQ45) and reviewed based on risks and returns comparison. The research took place since January 2012 until December 2016. This research is a descriptive research that was carried out with quantitative approach. The research population is 79 companies (issuers) that belong to the LQ 45 Index since February 2017 until January 2017. Sample selections were determined with purposive sampling technique with the criteria in which the stocks were actively traded and the data were consecutively available during the research period, which resulted in twenty-one stock samples. The methodology used in this research is the Single Index Model method. The result of the research shows that of the twenty-one sampled companies, fourteen of them configured an optimal portfolio. The proportions of the fund that configured an optimal stocks portfolio were ICBP 0,16201 (16,20%), TLKM 0,42355 (42,36%), INDF 0,23450 (23,45%), KLBF 0,17883 (17,88%), and GGRM 0,00111 (0,11%). The five stocks generated an expected return of about 0,02419 (2,42%) with the risks of it happening of about 0,01004 (1,00%). The calculations of ratio between the risk to return portfolio that was configured with the risk to return market (JKLQ45) shows that the risk to return portfolio performs better in comparison to the risk to return market portfolio (JKLQ45).